Method of synchronization and data processing from differents inertial sensors kits sources for the human gait analysis - Goźdź, Aleksandra; Kalinowski, Maciej; Kopniak, Piotr (Journal of Computer Sciences Institute, 2018)
The article talks about results of data synchronization measurements sourced from two recording gait systems for human gait analyses. Two systems are Xsens sensor kits: MT Awinda, Xbus Kit. The article cover file format used to save data and synchronization method for sensor measurement from above mentioned kits. On the basis of the studies carried out, sensor measurement from different places on human body are unify to a common frame of reference. The discussed method provides also progressive data processing for angles range from -180° to 180° conversion to the absolute angle value from initial sensor settings.